2020
DOI: 10.1186/s12906-020-03096-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of anthocyanins enhances the apoptosis of colon cancer cells by handicapping energy metabolism

Abstract: Background While anthocyanins are proven to be effective in inhibiting tumour cell proliferation, the underlying mechanisms remain unclear. This research aims to explore the glycosylation of anthocyanins in the tumour inhibitory effects and the potential mechanism. Methods The tumour inhibitory effect on mouse colon cancer cells (MC38) was examined by MTT and flow cytometric analyses. The inhibitory pathway of anthocyanin was explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Bilberry showed an antiproliferation effect in HT-19 cells and the mechanisms associated with increasing the expression of p21 [38][39][40]. Bilberry anthocyanin extract induced mitochondrial damage, activated apoptosis, inhibited cell proliferation in the mouse colon cancer cell line MC38 [41]. Bilberry extract has the potential to reduce the side effects of some chemotherapy drugs by suppressing the activity of topoisomerase I and the DNA strand breaks [42].…”
Section: Bilberrymentioning
confidence: 99%
“…Bilberry showed an antiproliferation effect in HT-19 cells and the mechanisms associated with increasing the expression of p21 [38][39][40]. Bilberry anthocyanin extract induced mitochondrial damage, activated apoptosis, inhibited cell proliferation in the mouse colon cancer cell line MC38 [41]. Bilberry extract has the potential to reduce the side effects of some chemotherapy drugs by suppressing the activity of topoisomerase I and the DNA strand breaks [42].…”
Section: Bilberrymentioning
confidence: 99%
“…These results suggested that O-glycosylation of flavonoids at the C-7 position could enhance their cytotoxic activities. Transmembrane delivery of flavonoid glycosides was reported to be carried out by glycoside binding to glucose transporters on the cell membrane [47]. Sodium-glucose cotransporter 1 and glucose transporter 2 mediated the cross-membrane transport of quercetin-3-O-glucoside and cyanidin-3-O-glucoside in Caco-2 cells [48].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Previous studies have shown that in a damaged cell model, anthocyanins with the monosaccharose substitution dissolved in DMSO had a significantly stronger protective effect than those with the disaccharide substitution against oxLDL-induced endothelial injury associated with increased cell viability, promoted NO release, and so on [ 21 ]. Analogously, C3 position glycosylation on anthocyanin dramatically increased its inhibitory effect on tumor cells [ 22 ]. Consistent with these observations, M3G was more effective than MV and M3,5G in reducing cytotoxicity when applied to KGN cells exposed to Cd, indicating that the monosaccharose structure has a stronger protective effect against Cd damage.…”
Section: Discussionmentioning
confidence: 99%